Naturam naturandum - Silva Guevara, Lizardo (2021)
The identification of God with substance on Spinoza’s writings comes from his interpretation of cartesian philosophy, in as much as he understands substance as necessary instead of taking it in its essentialist sense. Thus, there’s a scholastic distinction between substantial existence and necessary existence. This same distinction would be the one referred to in Descartes’ Principia Philosophiae concerning his definition of substance; nevertheless, Spinoza interprets them as equivalent. In this way, Spinoza identifies substance, on its essentialist sense, with the feature of necessity of the divine being; all of this in his Etica ordine geometrico demonstrata. This results on the identification of God with substance, because he is indeed the only substantial being that gathers all the distinct attributes expressed in many modes.